Preparation and characterization of polyaniline/Turkish Huntite-hydromagnesite composites - (:unkn) unknown (My University, 2014)
The aim of this study was to improve thermal stability of polyaniline (PANI) by adding Turkish Huntite. PANI was synthesized and PANI/Turkish Huntite composites were prepared by adding various proportions of huntite to aniline. The chemical structures of the samples were investigated by Fourier transform infrared spectroscopy. Thermal properties of the composites were determined by thermogravimetric analysis and differential scanning calorimetry. The surface morphologies of the samples were investigated by a scanning electron microscopy. The obtained results proved that the composite system is more thermally stable than the pure PANI. POLYM. COMPOS., 35:456-460, 2014. © 2013 Society of Plastics Engineers © 2012 Society of Plastics Engineers.